2017
DOI: 10.24001/ijaems.3.12.3
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Relationship between Work Engagement and Job Satisfaction in Private Companies in Kurdistan

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 15 publications
0
63
0
2
Order By: Relevance
“…The development of an organizational climate shows the organization's willingness to create organizational requirements in order to plan a successful application that will boost innovation potential. The frameworks used by organizations are diagnostic indicators for determining the magnitude of an organization's management capability in terms of preparing an environment that encourages empowerment and innovation (Anwar & Qadir, 2017). The empowerment strategy is used in this study as a philosophy to activate innovation in organizations.…”
Section: Introductionmentioning
confidence: 99%
“…The development of an organizational climate shows the organization's willingness to create organizational requirements in order to plan a successful application that will boost innovation potential. The frameworks used by organizations are diagnostic indicators for determining the magnitude of an organization's management capability in terms of preparing an environment that encourages empowerment and innovation (Anwar & Qadir, 2017). The empowerment strategy is used in this study as a philosophy to activate innovation in organizations.…”
Section: Introductionmentioning
confidence: 99%
“…The findings proved that there is a positive and significant direct and indirect relationship between environment of the change and strategic success, moreover change event has a positive and significant mediating role between environment of the change and strategic success. Table (7), illustrates the findings of Sobel test to find the mediation analysis, the result demonstrates the direct relationship between environment of the change and strategic success, P-value =.000 this indicated that there is a significant and positive direct relationship between environment of the change and strategic success. Furthermore, P-value is .000 as indirect relationship between environment of the change and strategic success.…”
Section: Analysis and Resultsmentioning
confidence: 89%
“…The beneficiaries of change are (Anwar & Abd Zebari, 2015) encouraged to engage in the decision-making process under the change management model. According to the change management view, nothing can change without the involvement of change recipients (Anwar & Qadir, 2017). In other words, according to the change management viewpoint, reform and change programs must "ultimately result in improvements in the operating processes of hospitality organizations, as well as in the attitudes and actions of workers working in those organizations" in order to have some effect (Anwar & Surarchith, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It is required that an infrastructure-and operations modelling technique is applied to a KM architecture to ensure continued success. Lee and Choi state that KM enabblers are measures that can be used by businesses to drive higher levels of consistency of information usage (Anwar & Qadir, 2017). After KM, then firms must focus on shared understanding.…”
Section: Knowledge Managementmentioning
confidence: 99%